1997
DOI: 10.1346/ccmn.1997.0450212
|View full text |Cite
|
Sign up to set email alerts
|

Beidellite and Associated Clays from the Delamar Mine and Florida Mountain Area, Idaho

Abstract: Abstract--There has been much interest in the rare specimen of beidellite from the Black Jack Mine, Florida Mountain, Idaho. A variety of aluminous clays exists along veins such as the Black Jack vein, in rhyolite and latite flows, and in near-surface ash beds, often containing less than 1.0% MgO and 0.5% Na20. Associated clays include beidellite, illite, kaolinite, 10-A halloysite, dickite, nacrite, rectorite and a tarasovite-like mineral. The predominant clay is mixed-layer illite-beidellite. The beidellites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 11 publications
0
31
1
Order By: Relevance
“…The similarities in XRD data between Ayvaclk, the Black Jack Mine, Idaho and DeLamar Mine, Idaho (Post et al, 1997) beidellites are shown in Table 1.…”
Section: Xrd Studiesmentioning
confidence: 96%
See 2 more Smart Citations
“…The similarities in XRD data between Ayvaclk, the Black Jack Mine, Idaho and DeLamar Mine, Idaho (Post et al, 1997) beidellites are shown in Table 1.…”
Section: Xrd Studiesmentioning
confidence: 96%
“…Most iron-rich, high-charge beidellites in verti- (Weir and Greene-Kelly, 1962) and DeLamar Mine, Idaho (Post et al, 1997 (Badraoui et al, 1987;Badraoui and Bloom, 1990). They also reported that during weathering, soil mica is transformed first to vermiculite and then to beidellite, preserving the tetrahedral character of the charge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to SWy-1 montmorillonite studied by Ferrage et al (2005b) (Post et al 1997 For all samples, size fractionation to < 1 µm was obtained by centrifugation. Then, ion exchange was achieved with 1 mol.L -1 aqueous solutions of CaCl 2 , for SAz-1 only, and SrCl 2 , with three steps of saturation followed by three washing steps, as described by Ferrage et al (2005b).…”
Section: Sample Preparationmentioning
confidence: 99%
“…The near complete swelling of layers following EG solvation is observed for montmorillonite and for population A of beidellite. In contrast, for beidellite increasing layer charge from the mean layer charge may produce vermiculite-like layers, discrete illite layers or irreversibly collapsed K-beidellite layers when potassium is present as assumed for SbId-1 (Post et al 1997). However, heterogeneous structures where layers have different hydration/swelling abilities is not a priori characteristic of smectite with layer charge originating in the tetrahedra, although such interstratified structures probably occur more frequently in beidellite compared to montmorillonite.…”
Section: Impurities In Beidellitesmentioning
confidence: 99%